2020
DOI: 10.21203/rs.2.24397/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SIK2 Promotes Cisplatin Resistance Induced by Aerobic Glycolysis in Breast Cancer Cells through PI3K/AKT/mTOR Signaling Pathway

Abstract: Objective This study aimed to investigate the effect of SIK2 on cisplatin resistance induced by aerobic glycolysis in breast cancer cells and its potential mechanism. Methods qRT-PCR and Western blot were used to detect SIK2 mRNA and protein levels. Cisplatin (DDP) resistant cell lines of breast cancer cells were established, CCK-8 was used to measure and evaluate the viability, and Transwell was used to evaluate the cell invasion capability. Flow cytometry was adopted to evaluate the apoptosis rate. The glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Similarly, also mechanical cues [93] and hypoxia or pseudohypoxia [56 , 94] can promote glycolysis-induced drug resistance. As regards cell-autonomous stimuli, oncoproteins, whether mutated or overexpressed [39 , 47 , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , tumor-associated immune checkpoint molecules [45] and long noncoding (lnc) RNAs/micro (mi) RNAs [16] are examples of stimuli that induce glycolysis-associated drug resistance.
Fig.
…”
Section: Stimuli Promoting Glycolysis-induced Drug Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, also mechanical cues [93] and hypoxia or pseudohypoxia [56 , 94] can promote glycolysis-induced drug resistance. As regards cell-autonomous stimuli, oncoproteins, whether mutated or overexpressed [39 , 47 , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , tumor-associated immune checkpoint molecules [45] and long noncoding (lnc) RNAs/micro (mi) RNAs [16] are examples of stimuli that induce glycolysis-associated drug resistance.
Fig.
…”
Section: Stimuli Promoting Glycolysis-induced Drug Resistancementioning
confidence: 99%
“…Many of these stimuli lead, directly or indirectly, to the activation of transcription factors that induce the expression of genes encoding glycolytic enzymes. In this regard, the phosphoinositide 3-kinase (PI3K)-AKT-mechanistic target of rapamycin (mTOR) signaling pathway [98 , 103 , 104] as well as the transcription factors hypoxia-inducible factor (HIF)-1α and c-Myc [67 , 94 , 96 , 105] play a prominent, but not exclusive [106] role.…”
Section: Stimuli Promoting Glycolysis-induced Drug Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that salt-inducible kinase 2 (SIK2) is upregulated in breast ( 20 ), ovarian ( 21 ) and cervical cancer ( 22 ), and promotes cancer progression, thus suggesting that SIK2 may act as an oncogene. To the best of our knowledge, the role of SIK2 in CRC has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%